Histological and Biochemical Study on Mitigation of Dichlorvos-Induced Hepatotoxicity by Mimosa Pudica in Mice - Linus Anderson Enye; Angel Keboh; Edem Edem; Olusola S Saka; Gabriel Godson Akunna (International Journal of Human Anatomy, 2020)
Objective Exposure of dichlorvos-contaminated foods, water and environment can lead to decrease in proper liver function. Thus, Mimosa pudica(MP)is being investigated in the present study to determine its protective effect on dichlorvos induced hepatotoxity in Mice. Methods Fifty adult male BALB/c mice weighing between 20-30g were randomly assigned into 5 groups of 10 animals each (Groups A, B, C, D, and E). Group A as the control Group received normal feed, group B received 0.1 ml of MP, group C was given 40 g of 2.5% Dichlorvos (DDVP) for 28 days. While, group D were given 40 g of 2.5% DDVP with 0.1ml of MP and group E animals were given DDVP for half the period of administration, normal feed and 0.1ml MP for 14 days. Histological and biochemical preparations of the liver were processed and data were expressed as mean± SEM. Significant difference was set at p<0.05. Results ALT activity and the total protein level of the liver show no significant increase (P < 0.005) when compared with the control. AST and ALP activities were significantly increased in animals given DDVP with subsequent MP treatment when compared with the controls. Histological studies revealed distortion of normal hepatic histoarchitecture in DDVP group B and MP groups mitigated these changes in the treated groups. Conclusion Dichlorvos caused tissue distortion in the mice with prominent toxic effects on the liver while MP extract showed ameliorative effects on the liver that was exposed to DDVP
Keywords: Histochemical